PREDICTORS OF ADVERSE LEFT VENTRICULAR REMODELING IN PATIENTS AFTER MYOCARDIAL INFARCTION - Zharikova, E.S.; Villevalde, S.V.; Kobalava, Z.D. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Medit͡s︡ina, 2017)
Functional recovery or irreversible negative remodeling of injured myocardial segments has different prognostic implication in patients with myocardial infarction (MI) undergoing coronary percutaneous intervention (PCI). Increased pulse wave velocity (PWV), a non-invasive index of arterial stiffness, is one of the important risk factors of cardiovascular events in different clinical conditions. The aim of the study was to assess the relationship between PWV and changes of left ventricular (LV) systolic function in patients with acute MI. Adverse cardiac remodeling was revealed in 72% of patients and they more often had non-recovery of left ventricular longitudinal function. Higher baseline PWV is associated with less effective recovery of LV function.